DEIXIS IN THE SONG LYRIC “LEVEL OF CONCERN” BY TWENTY ONE PILOTS - Siti Nurjamilah; Efransyah Efransyah (PROJECT (Professional Journal of English Education), 2021)
The title of this research is deixis in the Song Lyrics “Level of Concern” by Twenty One Pilots. The objectives of this research are to identify the type of deixis and to find out the dominant types of deixis that are mostly used in the song lyrics entitled Level of Concern. This research used descriptive qualitative method. The researchers took the data from (Joseph, 2020) of the song lyric entitled “Level of Concern” by Twenty One Pilots, for it describes the current world situation, and the lyrics of the song contains a wide range of deixis that have attracted the researchers to examine this song. After conducting this research, the researchers concluded that three types of deixis namely personal, spatial, and temporal deixis. Personal deixis divided into three parts: the first person as speaker, the second person as hearer and the third person as others, with 77 words in that song. Temporal deixis showed a certain period of time which consist of 3 words, and the spatial deixis describes the location in a conversation which consist of  2 words. The major type from the whole data are personal deixis, because they represent the singer and the message which wanted to be delivered to the listeners. Keywords:  Pragmatic, Deixis, Song Lyric